E-learning module for reproductive technologies, including mass synchronization and artificial insemination, for sheep and goats in Ethiopia - CGIAR Research Program on Livestock (2021)
This E-leaning course is aimed at increasing reproductivity of sheep and goat in low input systems. It is intended to be used by a variety of stakeholders in sheep and goat production, inclusive of livestock keepers, veterinarians, research institutes and universities, amongst others.